2022
DOI: 10.1080/19490976.2021.2022442
|View full text |Cite
|
Sign up to set email alerts
|

High-sugar, high-fat, and high-protein diets promote antibiotic resistance gene spreading in the mouse intestinal microbiota

Abstract: Diet can not only provide nutrition for intestinal microbiota, it can also remodel them. However, is unclear whether and how diet affects the spread of antibiotic resistance genes (ARGs) in the intestinal microbiota. Therefore, we employed selected high-sugar, high-fat, high-protein, and normal diets to explore the effect. The results showed that high-sugar, high-fat, and high-protein diets promoted the amplification and transfer of exogenous ARGs among intestinal microbiota, and up-regulated the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 67 publications
1
20
0
Order By: Relevance
“…Moreover, the significant shifts in the gut microbial composition after mcr-1 addition, and the increase in the abundance of genes enriched in plasmid transfer and diffusion pathways, formed an intestinal microenvironment that might promote the spread of ARGs. 36 These ARGs biomarkers were distributed in different bacteria, especially probiotics, opportunistic pathogens, and intestinal symbionts, which might interact with the host and result in damaged health.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the significant shifts in the gut microbial composition after mcr-1 addition, and the increase in the abundance of genes enriched in plasmid transfer and diffusion pathways, formed an intestinal microenvironment that might promote the spread of ARGs. 36 These ARGs biomarkers were distributed in different bacteria, especially probiotics, opportunistic pathogens, and intestinal symbionts, which might interact with the host and result in damaged health.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory host responses triggered by the gut immune system (in inflammatory bowel disease patients) or by pathogens can suppress the anaerobic microbiota and boost enterobacterial colonization densities [ 63 , 64 ]. The increasing prevalence of carbapenemases and extended-spectrum beta-lactamase in the opportunistic pathogenic bacteria E. coli and K. pneumoniae is readily transmitted in Proteobacteria in the gut [ 65 ]. In a streptomycin-treated mouse model of Salmonella infection, mouse intestinal inflammation promotes the coproliferation of donor and recipient bacteria in the gut [ 66 , 67 ].…”
Section: In Vivo Horizontal Gene Transfer Of Bacterial Resistancementioning
confidence: 99%
“…e increasing prevalence of carbapenemases and extended-spectrum beta-lactamase in the opportunistic pathogenic bacteria E. coli and K. pneumoniae is readily transmitted in Proteobacteria in the gut [65]. In a streptomycin-treated mouse model of Salmonella infection, mouse intestinal inflammation promotes the coproliferation of donor and recipient bacteria in the gut [66,67].…”
Section: Horizontal Transfer Of Antibiotic Resistance Genes In Thementioning
confidence: 99%
“…Some studies have reported that through the intestinal microbiota, HFHS influences the gut-brain axis and plays an important role in affecting the secretion of gonadal hormone levels [ 19 ]. Tan et al found that in mice colonized with fecal microbiota from women with polycystic ovarian syndrome (PCOS), the ovarian function was altered following fecal microbiota transplantation [ 15 ]. Past studies showed that cisplatin-induced POF was associated with the intestinal microbiota [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have demonstrated that intestinal microbiota plays a significant role in regulating host metabolism, immunity, intestinal barrier, and gut homeostasis [14]. Previous studies have proved that HFHS can alter the intestinal microbiota and affect the health of the host [15][16][17][18]. Some studies have reported that through the intestinal microbiota, HFHS influences the gut-brain axis and plays an important role in affecting the secretion of gonadal hormone levels [19].…”
Section: Introductionmentioning
confidence: 99%